Petrological diversity of continental arc magmatism evidenced by Triassic magmatic complexes in East Kunlun Orogen - Jie Gan; Wei Wang; Dongdong Yan; Hu Zhou; Fuhao Xiong; Huailai Zhou; Hui Li (Scientific Reports)
Abstract Understanding the petrogenetic relationships among the synplutonic dikes, magmatic enclaves and plutons in subduction zones provides key insights into the petrological diversity of arc magmatism. Here we present an integrated study on the petrology, LA–ICP–MS zircon U–Pb geochronology, whole-rock geochemistry and Sr–Nd–Hf isotopes of Triassic coeval basic-intermediate dikes, mafic microgranular enclaves (MMEs) and their host plutons (gabbrodiorite, granodiorite and monzogranite) in the East Kunlun Orogen, northern Tibetan Plateau, to reveal their magma sources, magmatic processes and dynamic connections. Petrological and chronological studies reveal that these mafic-felsic igneous rocks coexist in space and time, showing imprints of mixing or mingling and similar crystallization ages (ca. 248–242 Ma), forming a typical synplutonic complex. Geochemically, the synplutonic complex shows continuous compositional variations with varying SiO2 (44.22–76.56 wt%), whole–rock Sr–Nd and zircon Lu–Hf isotopic compositions ((87Sr/86Sr)i = 0.707521 to 0.717628, εNd(t) = -6.66 to 1.84, εHf(t) = -7.86 to 2.73). Petrogenetic research indicates that crust-mantle magma mixing and fractional crystallization respectively play crucial roles in their petrological and geochemical diversity. The mantle-derived mafic end-member, represented by the mafic dikes, originated from the partial melting of the sub-arc mantle wedge that metasomatized by subduction-related fluids. The crust-derived felsic end-member, represented by the monzogranite pluton, was sourced from the Mesoproterozoic metapelite-like continental basement of the East Kunlun Orogen. The mantle-derived mafic magma underplated the felsic lower continental crust, triggering its melting to form the felsic magmatic end-member. Subsequently, the crust-mantle magma end-members interacted mechanically or chemically in various proportions, forming the parental magmas of the cogenetic MMEs, intermediate dikes and gabbrodiorite to granodiorite plutons. This study demonstrates that mechanical or chemical mixing and subsequent fractional crystallization of crust-mantle magmas are significant mechanisms responsible for the petrological and geochemical diversity of continental magmatic arcs.